A Case of Lung Cancer with Venous Thromboembolism with Pre-Extensively Drug-Resistant Pulmonary Tuberculosis: A Rare Triad - Unnati Desai; Ketaki Utpat; Kriti Agarwal; Magizh Samuel (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
This case study describes the case of a patient with lung cancer who developed pre-extensively drug-resistant pulmonary tuberculosis and venous thromboembolism. We discuss how lung cancer can predispose an individual to pulmonary tuberculosis and venous thromboembolism.